Silica coated iron oxide nanoparticles-induced cytotoxicity, genotoxicity and its underlying mechanism in human HK-2 renal proximal tubule epithelial cells - Královec, Karel; Havelek, Radim; Zelinková, Eliška; Kučírková, Lucie; Hauschke, Martina; Bartáček, Jan; Palarčík, Jiří; Sedlák, Miloš (Elsevier Science Inc., 2019)
Iron oxide nanoparticles (IONPs) have a great potential with regard to cell labelling, cell tracking, cell separation, magnetic resonance imaging, magnetic hyperthermia, targeted drug and gene delivery. However, a growing body of research has raised concerns about the possible unwanted adverse cytotoxic effects of IONPs. In the present study, the in vitro cellular uptake, antiproliferative activity, cytotoxicity, genotoxicity, prooxidant, microtubule-disrupting and apoptosis-inducing effect of Fe3O4@SiO2 and passivated Fe3O4@SiO2-NH2 nanoparticles on human renal proximal tubule epithelial cells (HK-2) have been studied. Both investigated silica coated IONPs were found to have cell growth-inhibitory activity in a time- and dose-dependent manner. Determination of cell cycle phase distribution by flow cytometry demonstrated a G1 and G2/M phase accumulation of HK-2 cells. A tetrazolium salt cytotoxicity assay at 24 h following treatment demonstrated that cell viability was reduced in a dose-dependent manner. Microscopy observations showed that both Fe3O4@SiO2 and Fe3O4@SiO2-NH2 nanoparticles accumulated in cells and appeared to have microtubule-disrupting activity. Our study also revealed that short term 1 h exposure to 25 and 100 mu g/mL of silica coated IONPs causes genotoxicity. Compared with vehicle control cells, a significantly higher amount of gamma H2AX foci correlating with an increase in DNA double-strand breaks was observed in Fe3O4@SiO2 and Fe3O4@SiO2-NH2-treated and immunestained HK-2 cells. The investigated nanoparticles did not trigger significant ROS generation and apoptosis-mediated cell death. In conclusion, these findings provide new insights into the cytotoxicity of silica coated IONPs that may support their further safer use.
Silikou obalené nanočástice oxidu železa-indukují cytotoxicitu, genotoxicitu a mechanismus jejich působení u lidských epiteliálních buněk proximálního tubulu ledvin HK-2
Keywords: Magnetic nanoparticles; Kidneys; Cytotoxicity; DNA damage; ROS; Magnetické nanočástice; Ledviny; Cytotoxicita; Poškození DNA; ROS